Synthetic antimicrobial peptides Bac-5, BMAP-28, and Syn-1 can inhibit bovine respiratory disease pathogens in vitro - Cornejo, Santiago; Barber, Cassandra; Thoresen, Merrilee; Lawrence, Mark; Seo, Keun Seok; Woolums, Amelia (Frontiers in Veterinary Science, 2024)
Mass treatment with antibiotics at arrival has been the mainstay for bovine respiratory disease (BRD) control but there is an increase in antimicrobial-resistant bacteria being shed from treated cattle. BRD is a disease complex that results from the interaction of viruses or bacteria and susceptible animals with inappropriate immunity. With bacteria being the only feasibly treatable agent and the emergence of antimicrobial resistance, decreased efficacy of commonly used antibiotics could threaten livestock health. There is a need for new antimicrobial alternatives that could be used to control disease. Naturally occurring antimicrobial peptides (AMP) have been proposed to address this need. Here we tested the effect of bovine myeloid antimicrobial peptide-28 (BMAP-28), a synthetic BMAP-28 analogue Syn-1, and bactenecin 5 (Bac-5) on Mannheimia haemolytica (Mh) using a quantitative culture method and the clinical & laboratory standard institute guidelines to calculate the minimum inhibitory and bactericidal concentrationsbroth microdilution method to determine minimum inhibitory and bactericidal concentrations (MIC and MBC). We also tested the antiviral effect of these AMP against bovine herpes-1 (BHV-1) and bovine respiratory syncytial virus (BRSV) using the Reed and Muench method to calculate the viral titers after treatment. We demonstrated that BMAP-28 and Syn-1 can inhibit Mh growth and BMAP-28 can inhibit replication of BHV-1 and BRSV. Moreover, we showed that BMAP-28 and Bac-5 can be used together to inhibit Mh growth. When used alone, the MIC of BMAP-28 and Bac-5 was 64 and 128 µg/ml respectively, but when applied together, their MIC ranged from 0.25-16 for BMAP-28 and 8-64 µg/ml for Bac-5, resulting in a decrease in concentration of up to 256 and 16-fold respectively. The synergistic interaction between those peptides resulted in concentrations that could be well tolerated by cells. Our results demonstrate that bovine cathelicidins could be used as alternatives to antimicrobials against Formatted: Indent: Left: 10 mm, No bullets or numbering BRD pathogens. These findings introduce a path to discovering new antimicrobials and determining how these peptides could be tailored to improve cattle health.